Distance computation using Axis Aligned Bounding Box (AABB) parallel distribution of dynamic origin point - Sulaiman, Hamzah Asyrani; Bade, Abdullah; Abdullah, Mohd Harun (2013)
Performing accurate and precise collision detection method be-tween objects in virtual environment application such as computer games and medical simulation is important in computer graphics research and development. Given pair of objects that near colliding, numerous mechanic has been developed by researchers in order to minimize computation time and increase accuracy of the detection. However, most of these techniques required a lot of computational cost, extra processing power and complex algebraic equations just to solve distance between near colliding objects. In this paper, we described an alternate technique, which is a theoretical framework of novel technique in order to find the optimum closest distance between two or more convex polyhedral in virtual environment application. Given pair of near colliding objects, we proposed an easy to implement mechanism using dynamic origin point by creating inner and middle Axis Aligned Bounding-Box just to find closest distance between objects. We believed that the technique is suitable to be used in any game engine tools for computer games and medical simulation.